2022
DOI: 10.1177/02654075221093611
|View full text |Cite
|
Sign up to set email alerts
|

Relationship difficulties and “technoference” during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has touched many aspects of people’s lives around the world, including their romantic relationships. While media outlets have reported that the pandemic is difficult for couples, empirical evidence is needed to test these claims and understand why this may be. In two highly powered studies ( N = 3271) using repeated measure and longitudinal approaches, we found that people who experienced COVID-19 related challenges (i.e., lockdown, reduced face-to-face interactions, boredom, or worry) al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In line with Zoppolat et al (2022) , the research examining technology use specifically for social connection during the pandemic did so in relation to COVID-19-related guidelines (a specific external stressor, according to Pietromonaco & Overall’s (2021) adapted VSA model). Interesting indirect and direct links emerged between these sets of variables.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 84%
See 1 more Smart Citation
“…In line with Zoppolat et al (2022) , the research examining technology use specifically for social connection during the pandemic did so in relation to COVID-19-related guidelines (a specific external stressor, according to Pietromonaco & Overall’s (2021) adapted VSA model). Interesting indirect and direct links emerged between these sets of variables.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 84%
“…Increased technology use—specifically, phone use and social media engagement—appear to have impacted romantic relationships during the pandemic. In two highly powered studies ( N = 3271), researchers ( Zoppolat et al, 2022 ) found that people who experienced COVID-19 related challenges (i.e., lockdown, reduced FtF interactions, boredom, worry) also reported greater self and partner phone use and time spent on social media. In turn, couples experienced more conflict and less relationship satisfaction.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…Additionally, our study explored the mechanism of technoference in conjugal interactions on child smartphone dependence from the perspective of family relationship and parenting, but there may be other personality and relationship variables that are yet unexplored that may be causal, moderating or mediating factors in the relationship between technoference in conjugal relationships and child smartphone dependence. According to the Interaction of Person-Affect-Cognition-Execution (I-PACE) model of specific internet-use disorders [ 76 ], there may be some mediation or mediation mechanism that explained how technoference in conjugal interactions might accelerate child smartphone dependence through personal emotional and cognitive factors, such as depression [ 22 ], couples’ distraction with technology, emotional stability [ 77 ], and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that technoference in conjugal interactions has a great impact on family ecology. On the one hand, in the context of couples interacting, technoference can cause conflicts [ 22 ] and damage the marital relationship [ 16 , 23 ]. Contemporarily, conflicts in couples and the destruction of relationships will lead to the deterioration of the family atmosphere, which will create pressure for children.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation